Adaptation and identity shifts after migration and return migration: Turkish qualified returnees from Germany and the US - Yilmaz Sener, Meltem (Border Crossing, 2020)
This study looks at the adaptation experiences of Turkish qualified migrants who returned to Turkey after living in Germany and the US, discussing their identity shifts both during the period spent in the host country and after the return. I look at their i- pre-migration familiarity with the language and culture of the host country, ii- social groups in the host country, iii- association memberships in the host country, iv- frequency of their visits to Turkey, v- the extent to which they followed the developments in Turkey, vi- reasons behind the decision to return, vii- re-adaptation to the home country culture after return, and viii- relationships with other returnees and host country nationals after return. By focusing on these aspects of their experiences, I aim to demonstrate the kinds of orientations they have had to the host and home country cultures, and the identity shifts they had both after migration and return. I also discuss whether there are any differences between the returnees from Germany and the US in terms of these dimensions.